PERAN BPD DALAM PENGEMBANGAN MSDM DAN POTENSI DESA DI DESA PLANDAAN, KEDUNGWARU TULUNGAGUNG - Eko Santoso; Bondan Subagyo; Desi Rahmawati (JANITA : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
The aim of establishing a swimming pool in Plandaan Village is to develop the potential of a tourist village through the construction of a swimming pool, considering that the swimming pool is a tourist destination that is popular with children and a comfortable place to play with the family. The existence of a swimming pool in Plandaan Village can meet the needs of the community, both within Plandaan Village and outside Plandaan Village City. Therefore, through the results of the Village Deliberation, the existence of the swimming pool in Plandaan village needs to be developed and utilized as a tourist area. This is none other than to develop the potential of the local village area. Apart from that, the swimming pool in Plandaan Village can also increase activities for young people to become a field of work and increase the income of the local Plandaan Village area, because it will also directly increase the cash of Plandaan Village. The results of developing the potential of the Plandaan Village area regarding the construction of a swimming pool can be collaboration and cooperation with school agencies for swimming sports activities. Apart from that, it is also a tourist area that needs to be developed and enlivened considering that the existence of this swimming pool is very strategic in the Plandaan Village area. However, the existing activities This swimming pool must also be managed professionally in order to attract more visitors, not only in the local Plandaan area, but also outside the village of Plandaan itself. Promotions and services must be improved to attract visitors who will come to the swimming pool. Also, the presence of clean bathroom facilities will attract future visitors.